Morocco : Second Review Under the Arrangement Under the Precautionary and Liquidity Line-Staff Report; Press Release; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report, 2015)
EXECUTIVE SUMMARY The economy is recovering and the outlook is favorable but still subject to significant risks. After slowing to below 2 1\2 percent in 2014, growth is expected to be close to 5 percent in 2015, boosted by a strong agricultural output and a gradual acceleration of activity in other sectors. Fiscal policy is on track to achieve the annual deficit objective of 4.3 percent of GDP. The external position has improved rapidly, benefiting from lower oil prices and strong export performance. Inflation remains low. However, more remains to be done to reduce unemployment, especially among the youth. Assuming steadfast implementation of reforms, growth should gradually accelerate over the medium term. However, the outlook remains subject to the risks of a structurally weak growth in key advanced economies, tighter or more volatile global financial conditions, and increased volatility of energy prices. Important progress has been made on key reforms; sustaining these efforts will be important to foster higher and more inclusive growth. Significant progress was made in reforming the subsidy system, thereby reducing its costs and associated fiscal risks. At the same time, social programs on health and education were expanded. The adoption of the new organic budget law in May 2015 was a crucial step in improving the fiscal framework, while progress has also been made in upgrading the financial policy framework. Timely reform of the pension system is needed to ensure its viability while extending its coverage. Sustaining efforts to improve the business environment, competition, governance and transparency, as well as the functioning of the job market and the quality of education and vocational training, will also be important for increasing competitiveness, growth, and employment. The program remains on track and Morocco continues to meet the PLL qualification criteria. Both March 2015 quantitative indicative targets were met comfortably. Morocco continues to perform strongly in three out of the five PLL qualification areas, while not substantially underperforming in the fiscal and external areas. Staff recommends the completion of the second review under the arrangement.